Methodology of Teaching Arithmetic Practices in Primary School Mathematics - Fozilov Ibrokhimjon Rakhimovich; Qo'chqarova Mahmuda Adxamjonovna; Fozilov Jakhongir Ibrokhimovich (Zien Journals, 2022)
Below to bring which was in our minds primary class mathematics in classes arithmetic actions teaching methodology about information and suggestions listed
Keywords: Introduction classes; continuous education; mathematics; arithmetic actions